Trapping and Detrapping Effects on Current Conduction Mechanisms at Interface of Au/HfO2 High-k Films. Issue 12 (December 2015) - Yuqian, Zhang; Li, Fu
Abstract: The leakage current density-voltage properties of HfO2 high-k dielectrics annealed at different temperatures and the current conduction mechanisms under gate injection were studied in details. It is found that the leakage currents are mostly associated with the high trap density at the interface of Au/HfO2 under gate injection, and the dominant conduction mechanisms of Au/HfO2 /p-Si structure are the Schottky emission and Poole-Frenkel mechanism in the region of high electric fields. To study the reliability of the gate dielectric film, the capacitors were stressed at constant voltages under gate injection. Time dependent dielectric breakdown (TDDB) can be observed due to the formation of a percolation cluster under constant voltage stress.